INNOVATIVE TOOLS FOR STATE REGULATION OF SUSTAINABLE DEVELOPMENT OF THE CONSTRUCTION INDUSTRY - YERMOLENKO, Oksana; VILGIN, Yevhen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the use of innovative state regulatory instruments for the sustainable development of the construction industry. This industry is key to the Ukrainian economy, providing jobs and stimulating related sectors. The upcoming post-war recovery, Ukraine’s obligations to join the EU, and today’s global challenges highlight the need to rethink approaches to effectively regulating the construction industry. Traditional regulatory instruments do not always provide a stable balance of economic, environmental, and social interests, necessitating the implementation of innovative mechanisms of state influence focused on energy efficiency, greening of production, digitalization of processes, and the stimulation of responsible behavior by business entities. State support for the construction industry is a necessary condition for its further existence and development. As a result of the study, it was found that innovative instruments of state regulation play a key role in ensuring the sustainable development of the construction industry, as they enable the integration of economic efficiency, environmental safety, and social responsibility. The study showed that the comprehensive application of economic, institutional, environmental, digital, and social instruments of state regulation increases the competitiveness of the construction industry, reduces the negative environmental impact, and improves the quality of life of the population. At the same time, several restraining factors were identified, including institutional constraints, insufficient financial support for innovation, and fragmented regulatory and legal support. In view of this, further scientific research should be directed to the following areas: developing methodological approaches to assessing the effectiveness of innovative instruments of state regulation in the construction industry; deepening research on the adaptation of European practices of "green" and sustainable construction to national conditions.